POTENSI DAYA TARIK RIAM BERAWAT’N UNTUK WISATA ALAM DI DUSUN MELAYANG DESA SAHAN KECAMATAN SELUAS KABUPATEN BENGKAYANG - Rosadi, Paramita; Roslinda, Emi; dina, Wah (JURNAL HUTAN LESTARI, 2015)
Bengkayang district have many kind of natural resources and beauty, lead to many potency in ecotourism. The potency is not discovered yet and one of them is Riam Berawat’n that is found in Dusun Melayang Sahan Village Seluas Sub-District. This Riam has its own uniqueness with ± 98 min height and it has alegend. The aim of this researchis to findout the potency of Riam Berawat’n as ecotourism area. The research used descriptive qualitative method analyzed by certain scoring. The result showed that Riam Berawat’n have the value (B), in scoring which means it has enough potency to be developed into an ecotourism area with total value of 546,81. Keywords: Ecotourism potency, Riam Berawat'n, Bengkayang District